The Implementation Of Inquiry-Based Learning For TheTeaching Of English At Smp Muhammadiyah 4 SurakartaIn 2015/2016 Academic YearResearch Paper - Afani, Meisinta Nur; , Prof. Dr. Endang Fauziati, M. Hum; , Nur Hidayat, S.Pd, M.Pd (2016)
Afani, Meisinta Nur. A320120104. THE IMPLEMENTATION OF INQUIRY BASED LEARNING FOR TEACHING ENGLISH AT SMP MUHAMMADIYAH 4 SURAKARTA IN 2015/2016 ACADEMIC YEAR. Research Paper. Muhammadiyah University of Surakarta. 2016. The study is aimed to explain the implementation of Inquiry-based learning for teaching English at SMP Muhammadiyah 4 Surakarta in 2015/2016 academic year. The researcher gets data of this research from events, information and document. This research is describtive qualitative research. The method of collecting data is observation, interview and documentation. The techniques of data analysis is data reducation, display and conclusion drawing/verification. The results of the analysis show that: 1) For learning objective there are two kinds namely: general learning objective and specific learning objective. 2) In the classroom procedure, the researcher find that the teacher used Inquiry based learning in teaching English at 7D and 7E there are three steps Exploration, Elaboration and Confirmation. 3) The classroom technique that the researcher found during the observation such as oral repetition,identifying key-words, answering the questions, free writing, problem solving and reading passage. 4) The researcher found four kinds of Instructional materials during the observations, there are (a) textbook, (b) picture in the monitor, (c) slide of power point, and (d) video. 5) There are four of teacher's role that the researcher found in the SMP Muhammadiyah 4Surakarta during the observation, there are: (a) teacher are controller, (b) teacher as manager, (c) teacher as facilitator, (d) teacher as motivator. 6) There are four of students role that the researcher found in the SMP Muhammadiyah 4Surakarta during the observation, there are: (a) students as planner, (b) students as member, (c) students as performer, (d) students as monitor. 7) media that used in SMP Muhammadiyah 4 Surakarta, which is used in teaching learning process at 7 D and 7E such as: (a) picture, (b) Board, (c) computer, and (d) tape recorder. And 7) Type of Assessment tools used are daily test, midterm examination and final examination. Key words: Inquiry-Based Learning, teaching learning English.